Characteristics of spontaneously proliferating mononuclear cells in rheumatoid arthritis. Issue 5 (October 1984) - Froebel, K; Dickson, R; Lewis, D; Jasani, M K; Sturrock, R D
Abstract : The phenomenon of increased spontaneous incorporation of 3H-thymidine (3H-TdR) into peripheral blood mononuclear cells in rheumatoid arthritis (RA) has been investigated. The activity was found to be short lived and affected less than 1% of cells. Using a Percoll density gradient we identified two populations of active cells. RA patients with active synovitis and increased 3H-TdR incorporation in the low density population of cells have higher overall 3H-TdR incorporation than normal controls and patients with inactive RA. The low density cell population is enriched for Ia+ cells. The data are consistent with raised spontaneous 3H-TdR incorporation being due to an in-vivo cell mediated immune response.